A OBSERVASI PENELITIAN TENTANG PENDIDIKAN KARAKTER DI SDN 012 RAMBAH SAMO - anggela, sabariah (Jurnal Lazuardi, 2025)
This study aims to determine the implementation of character education at SD Negeri 012 Rambah Samo through learning activities and students' daily activities. The study used a non-participant observation method, focusing on the four main values ​​of character education: discipline, responsibility, honesty, and cooperation. Data were obtained through direct observation of student behavior and the role of teachers in guiding and implementing character habits. The observations indicate that the implementation of character education at the school is in the good category, characterized by fairly consistent discipline routines, the implementation of responsibilities through duty and completion of learning assignments, and student cooperation in group activities. However, the value of honesty still requires reinforcement, especially when students face learning evaluations. Teachers play an active role through role modeling, providing guidance, and positive reinforcement. Overall, character education at SD Negeri 012 Rambah Samo has been implemented quite effectively, although improvements in honesty and equitable student involvement in group work are still needed.